Role of NUCB2/nesfatin-1 as a Possible Biomarker - Aydin, Suleyman (Bentham Science Publ Ltd, 2013)
Nesfatin-1, discovered by Oh-I and his coworkers in 2006, is a multi-functional peptide hormone with an approximate MW of 9.8 kDa and a half-life of 23.5 minutes. This peptide is found in three different forms, nesfatin-1, nesfatin-2 and nesfatin-3, all three of which are formed from the precursor NUCB2 by proteolytic processing. The 30-amino acid middle segment of nesfatin-1 (M30) is responsible for limiting food intake, while the exact physiological role of nesfatin-2 and nesfatin-3 is unknown. This review will focus on nesfatin-1 in relation with tissue and fluid distribution, considerations for its analysis in body fluids, and its potential as a biomarker for some diseases.
Keywords: Nesfatin/nucleobindin 2; nesfatin-1; NUCB2; satiety; biomarker